Liberating God: Classical Theism and Political Spirituality - Hewitt, Simon (AGATHEOS – European Journal for Philosophy of Religion, 2024)
Accounts of spirituality are incomplete unless they take into account what I term political spirituality, the working out of religiously motivated political commitment. Working within the Christian tradition, I examine the interaction between political spirituality and God-concepts. My argument is that apophatic classical theism is better suited to underwriting political spirituality than are more recent non-classical doctrines of God. I lay out critiques of classical theism on the part of recent theologians and argue that, far from these critiques being decisive, there are positive reasons to favour apophatic classical theism for political reasons. I conclude by examining how the apophatic classical theist can engage with Marx’s critique of religion.